Analysis of surface water availability in the watershed river Piracicaba - MG (Research, Society and Development, 2021)
In view of the degradation of hydric resources and their unavailability, it becomes necessary to seek measures to promote the rational use and provide economic resources for their maintenance. The watershed of the Piracicaba River (MG), a tributary of the Doce River, suffers strong pressure on its water resources, mainly due to its economic profile, with mining and steelworks standing out. Therefore, the determination of water availability in the basin provides subsidies for the integrated management of the quantitative aspects of water resources. In this sense, the objective of this study was to determine the surface water availability in the Piracicaba river basin. For this, the list of surface water users was obtained from the Instituto Mineiro de Gestão das Águas (Igam) and later analyzed. Calculations of water availability were carried out stretch by stretch of the basin, as well as the calculation of the viability of regulating the flow of the stretches with water unavailability. As a result, 103 sections with unavailable water were identified in the study area, of these only 3 have no feasibility of flow regulation. The information on water availability should be periodically updated, in order to obtain a better scenario for the decisions of the basin's water management. It is recommended to include an analysis of underground abstractions with surface abstractions in studies of water availability in watershed.